The AdVance and AdVanceXP male sling in urinary incontinence: is there a difference? - Hüsch, Tanja; Kretschmer, Alexander; Nyarangi-Dix, Joanne (World journal of urology, 2018)
PurposeTo compare the efficacy and perioperative complications of the AdVanceXP with the original AdVance male sling.MethodsWe retrospectively enrolled 109 patients with an AdVance and 185 patients with an AdVanceXP male sling. The baseline characteristics and complication rates were analyzed retrospectively. Functional outcome and quality of life were evaluated prospectively by standardized, validated questionnaires. The Chi2-test for categorical and Mann-Whitney U test for continuous variables were performed to identify heterogeneity between the groups.ResultsRegarding operation time, there was no significant difference between the slings (p = 0.146). The complication rates were comparable in both groups except for postoperative urinary retention. This occurred significantly more often in patients with the AdVanceXP (p = 0.042). During follow-up, no differences could be identified regarding ICIQ-SF, PGI or I-QoL or number of pad usage.ConclusionsThe AdVance and AdVanceXP are safe and effective treatment options for male stress urinary incontinence. However, the innovations of the AdVanceXP sling did not demonstrate a superiority over the original AdVance sling regarding functional outcome.
Gesehen am 05.11.2019